Sensorless current mode control-an observer-based technique for DC-DC converters. - Midya, P. (IEEE Transactions on power electronics)
Sensorless current mode (SCM) control is an observer method that provides the operating benefits of current mode control without current sensing. SCM has significant advantages over both conventional peak and average current-mode control techniques in noise susceptibility and dynamic range in both continuous mode and discontinuous mode. The method supports line and bulk load regulation, and reduces control complexity to a single loop. It also supports conventional two-loop control for tight load regulation. Encompassing one-cycle control as a special case, the general SCM method is a public domain control technique